Water Quality Analysis on Public and Household Water Sources – A Case Study of Sunyani-West District, Fiapre - Antwi-Agyei, Prince; Otchere, Bernard; Ibn Idris Kofi Yeboah, Saeed; Odoi, Judith (Journal of Water, 2025)
Access to potable and quality water in most rural communities is low such that over 2.2 billion people worldwide are negatively affected. The increasing population in Fiapre and the inconsistent water supply by the Ghana Water Company Limited (GWCL) have forced most residents to resort to alternative groundwater sources such as boreholes, wells, etc. Yet, many residents use these sources of water unaware of the quality of the water and its potential health implications. This study assessed drinking water quality in Fiapre by calculating its Weight Average Water Quality Index (WAWQI) and investigating potential risk factors associated with contamination through a cross-sectional study and laboratory analysis of various physicochemical and microbiological water quality parameters. WAWQI was used to compute parameters using 10 factors including pH, electrical conductivity, temperature, TDS, phosphate, chloride, total hardness, nitrate, alkalinity, and faecal coliform. The findings revealed that the pH level of water, phosphate concentration, and fecal coliform count surpassed the recommended thresholds set by the World Health Organization (WHO) for safe drinking water. Although levels of electrical conductivity, TDS, nitrate, total hardness, and chlorine kept changing from one water source to another, the difference was not significant apart from phosphate and fecal coliform which shows a significant difference between the sachet water sources and other water sources (P<0.05). The study outcomes demonstrated that the overall water quality is predominantly categorized as good to fairly good, with the highest Water Quality Index (WQI) value reaching 87.84% and the lowest recorded at 54.81%. Therefore, to improve the water quality in the municipality, local management agencies should pay attention to the microbiological quality of the water sources. The study recommends regular handwashing practices, hygienic surroundings of the water source, and drinking water treatment to reduce the possible risk factors associated with the contamination of the water sources.
Keywords: Contamination; Risk; Physicochemical; Microbiological; Water quality